2017
DOI: 10.14202/vetworld.2017.1447-1455
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic and immune modulatory influences of Nigella sativa Linn. in broilers exposed to biological challenge

Abstract: Background and Aim:Prophylaxis and disease prevention is an essential strategy among biorisk management in poultry farms that stimulate and maintain the birds’ immunity. The aim of this study was to investigate the prophylactic, and immune-stimulant influence of Nigella sativa Linn. in broilers under biological stress.Materials and Methods:A total of 250 1-day-old (ross) chicks were divided into 5 groups; four of which were supplemented with 1.4%, 2.8%, 4.2%, and 5.6% N. sativa Linn., respectively. The four su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 30 publications
2
15
0
Order By: Relevance
“…The analysis of serum biochemical parameters gives an indication about the health, nutritional and physiological status of animals (Abd El-Hack and . In this study, the results of serum of liver and kidney function biomarkers, and TP and Glob levels were in agreement with the results of Khan et al (2012), Soliman et al (2017) and El-Hack et al (2018). The increase in serum TP may be referred to the immunostimulant effect of N. sativa (Al-Beitawi and El-Ghousein, 2008) and the availability of black cumin seed proteins in birds diets (Khan et al, 2012).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The analysis of serum biochemical parameters gives an indication about the health, nutritional and physiological status of animals (Abd El-Hack and . In this study, the results of serum of liver and kidney function biomarkers, and TP and Glob levels were in agreement with the results of Khan et al (2012), Soliman et al (2017) and El-Hack et al (2018). The increase in serum TP may be referred to the immunostimulant effect of N. sativa (Al-Beitawi and El-Ghousein, 2008) and the availability of black cumin seed proteins in birds diets (Khan et al, 2012).…”
Section: Resultssupporting
confidence: 88%
“…Additionally, RO significantly increased phagocytic activity and phagocytic index in broilers (Abd El-Latif et al, 2013). Moreover, black cumin may have an immunostimulant effect by increasing antibody titer against Newcastle disease (ND) and infectious Bursal disease as well as IgG and IgA contents in broilers challenged with E. coli and fed 4.2 or 5.6% N. sativa (Soliman et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The study revealed highly significant increase (p<0.01) in IgG and IgA in NS 4.2% and NS 5.6% fed groups, on the other hand, IgM showed non-significant difference in all groups. A highly significant (p<0.01) decline in total bacterial count and total Enterobacteriaceae count was also noticed in the NS 5.6% fed broilers (21) .…”
Section: In-vivo Studiesmentioning
confidence: 71%
“…Blood samples were collected, held at 37°C for 2 h, and centrifuged at 3500 rpm for 15 min. Clear sera were dispensed into Eppendorf tubes, tested for blood sugars, and stored at −20°C for biochemical, hormonal, and immunological analysis [18]. Birds were slaughtered after blood sampling; carcasses were weighed (total CW and expressed by CW/g), liver, heart, spleen, and bursa were removed, weighed, and expressed as g/kg.…”
Section: Methodsmentioning
confidence: 99%